2020
DOI: 10.3390/cancers12071862
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Hepatocellular Cancer Patients with Mild to Severe Liver Dysfunction: Adjunctive Role of the ALBI Grade

Abstract: Immune checkpoint inhibitors (ICI) have shown positive results in patients with hepatocellular carcinoma (HCC). As liver function contributes to prognosis, its precise assessment is necessary for the safe prescribing and clinical development of ICI in HCC. We tested the accuracy of the albumin-bilirubin (ALBI) grade as an alternative prognostic biomarker to the Child-Turcotte-Pugh (CTP). In a prospectively maintained multi-centre dataset of HCC patients, we assessed safety and efficacy of ICI across va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 44 publications
(52 reference statements)
3
50
0
Order By: Relevance
“…In HCC, the ALBI grade is superior to the CP grade in terms of assessing liver function reserve [26]. In addition, recent studies have demonstrated that the ALBI grade is associated with higher levels of AFP and more advanced tumor stage, which is correlated with malignant biological behavior and poor prognosis [32], similar to the association of AAPR in HCC. Moreover, HCC patients without cirrhosis, in whom HCC is presumably attributed to the direct carcinogenic effect of HBV infection, tend to harbor larger-sized or poorly differentiated tumors, contributing to the unfavorable prognosis of early-stage HCC [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…In HCC, the ALBI grade is superior to the CP grade in terms of assessing liver function reserve [26]. In addition, recent studies have demonstrated that the ALBI grade is associated with higher levels of AFP and more advanced tumor stage, which is correlated with malignant biological behavior and poor prognosis [32], similar to the association of AAPR in HCC. Moreover, HCC patients without cirrhosis, in whom HCC is presumably attributed to the direct carcinogenic effect of HBV infection, tend to harbor larger-sized or poorly differentiated tumors, contributing to the unfavorable prognosis of early-stage HCC [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…A multi-institutional dataset that included 427 patients with HCC treated with immune checkpoint inhibitors between 2017 and 2019 in 11 tertiary-care referral centres specialized in the treatment of HCC was analysed. Clinical outcomes of this patient cohort have been reported elsewhere 67,68 . Inclusion criteria were: 1) diagnosis of HCC made by histopathology or imaging criteria according to American Association for the Study of Liver Disease and European Association for the Study of the Liver guidelines; 2) systemic therapy with immune checkpoint inhibitors for HCC that was not amenable to curative or loco-regional therapy following local multidisciplinary tumour board review; 3) measurable disease according to RECIST v1.1 criteria at commencement of treatment with immune checkpoint inhibitors.…”
Section: A Validation Cohort Of Patients With Hcc Treated With Pd1-tamentioning
confidence: 99%
“…Given this study enrolled patients treated with ICI as part of routine clinical practice, our sample included patients with Child-Pugh B cirrhosis, largely excluded from clinical trials of ICI in HCC. While impaired liver function is a key prognostic determinant in HCC, 20 this was unrelated to the provision of CT and supplementary analyses inclusive of Child-Pugh A patients only were concordant with main study outcomes (online supplemental figures S3-4). We could not ascertain the relationship between CT and comorbidities other than liver dysfunction, an aspect worth exploring in prospective studies.…”
Section: Discussionmentioning
confidence: 76%